Positive electrode active material recycling method

By heat treatment, washing and annealing of the positive electrode waste of lithium secondary battery, the problems of environmental pollution and high cost of using acid extraction active materials in the prior art are solved, and environmentally friendly and economical reuse of active materials is achieved, and battery characteristics are restored.

CN115004451BActive Publication Date: 2025-04-01LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080094205.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-25
Filing Date
2020-11-06
Publication Date
2025-04-01
Estimated Expiration
2040-11-06

AI Technical Summary

Technical Problem

In the prior art, when collecting and reusing active materials from the positive electrode waste of lithium secondary batteries, acid is required for extraction, resulting in increased process costs and environmental pollution, and the inability to effectively collect lithium elements.

Method used

Reusable active material is obtained by heat-treating the positive electrode waste material including the lithium cobalt oxide positive electrode active material layer, removing the binder and conductive material, followed by washing and drying with an aqueous solution of lithium precursor, and finally annealing without adding additional lithium precursors.

Benefits of technology

The reuse of environmentally friendly active materials is achieved, the process cost is reduced, and all metal elements of the positive electrode active material can be collected, including lithium, and the battery characteristics of the active material are restored.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115004451B_ABST
    Figure CN115004451B_ABST
Patent Text Reader

Abstract

A method for collecting and reusing active materials from cathode waste is provided. The cathode active material recycling method according to the present invention comprises the following steps: (a) heat-treating cathode waste including a lithium cobalt oxide cathode active material layer on a current collector in air to thermally decompose a binder and a conductive material in the active material layer, thereby separating the current collector from the active material layer, and recovering the active material in the active material layer; (b) washing the recovered active material with an alkaline lithium precursor aqueous solution in an aqueous solution state, and drying; and (c) annealing the washed active material without adding additional lithium precursor to obtain a reusable active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for recycling resources in the manufacturing process of lithium secondary batteries. More specifically, the present disclosure relates to a method for collecting and recycling positive electrode waste generated in the manufacturing process of lithium secondary batteries or positive electrode active materials of lithium secondary batteries discarded after use. This application claims the benefit of Korean Patent Application No. 10-2020-0062372 filed with the Korean Intellectual Property Office on May 25, 2020, the disclosure of which is incorporated herein by reference in its entirety. Background Art

[0002] Rechargeable lithium secondary batteries are gaining attention as an alternative to fossil energy. Such lithium secondary batteries are mainly used in traditional handheld devices such as mobile phones, cameras, and power tools. Recently, the scope of application tends to be gradually expanded to vehicles driven by electricity (EV, HEV, PHEV), large-capacity energy storage systems (ESS), and uninterruptible power supply systems (UPS).

[0003] A lithium secondary battery includes: an electrode assembly including a unit cell, each of which includes a positive plate and a negative plate, the positive plate and the negative plate including a current collector and an active material coated on the current collector, a separator interposed between the positive plate and the negative plate; and a package or battery case, in which the electrode assembly is airtightly received together with an electrolyte solution. Lithium secondary batteries mainly include lithium-based oxides as positive electrode active materials and carbon-based materials as negative electrode active materials. Lithium-based oxides contain metals such as cobalt, nickel or manganese. In particular, cobalt, nickel and manganese are very expensive precious metals. Among them, cobalt is a strategic metal, and its supply is the focus of worldwide attention. Due to the limited number of cobalt producing countries, the global supply of cobalt is unstable. When the supply and demand of strategic metals are unbalanced, the cost of raw materials is likely to rise.

[0004] Research has been conducted on collecting and recovering precious metals from lithium secondary batteries (waste batteries) discarded after expiration. In addition to waste batteries, it is more preferable to collect resources from waste materials discarded after positive plates are punched out, or from positive plates that have defects or failures in the process.

[0005] Currently, if Figure 1 As shown in , a lithium secondary battery is manufactured by coating a positive electrode slurry including a positive electrode active material, a conductive material, a binder and a solvent on a long sheet type positive electrode collector 10 (such as aluminum (Al) foil) to form a positive electrode active material layer 20, manufacturing a positive electrode sheet 30, and punching a positive electrode plate 40 into a predetermined size. The remainder after punching is discarded as a positive electrode waste 50. If the positive electrode active material is collected and reused from the positive electrode waste 50, it will be very ideal in terms of industrial economy and environment.

[0006] Most of the existing methods for collecting positive active materials include dissolving the positive electrode with hydrochloric acid, sulfuric acid, nitric acid, etc., extracting active material elements such as cobalt, nickel, and manganese, and using them as raw materials for the synthesis of positive active materials. However, the use of acid to extract active material elements adopts a non-environmentally friendly process to collect pure raw materials, and requires a neutralization process and a wastewater treatment process, resulting in increased process costs. In addition, such a process is unlikely to collect lithium (one of the key positive active material elements). In order to overcome these shortcomings, a direct recycling method that does not dissolve the positive active material and does not extract the active material in elemental form is needed. Summary of the invention

[0007] Technical issues

[0008] The present disclosure is directed to providing a method for collecting and reusing active materials from cathode waste.

[0009] Technical Solution

[0010] In order to achieve the above-mentioned problem, a method for recycling positive electrode active materials comprises: (a) heat-treating positive electrode waste including a lithium cobalt oxide positive electrode active material layer on a current collector in air to thermally decompose a binder and a conductive material in the active material layer to separate the current collector from the active material layer, and collecting the active material in the active material layer; (b) washing the collected active material with an aqueous lithium precursor solution that is alkaline in aqueous solution, and drying; and (c) annealing the washed active material without adding additional lithium precursor to obtain a reusable active material.

[0011] The heat treatment may be performed at 300° C. to 650° C. for 1 hour or less.

[0012] The heat treatment may be performed at 550° C. for 30 minutes with a temperature rise rate of 5° C. / minute.

[0013] The washing may be performed by stirring the collected active material while being immersed in the lithium precursor aqueous solution.

[0014] The content of the lithium precursor in the lithium precursor aqueous solution may be 0% or more and 15% or less, and the lithium precursor preferably includes LiOH. The washing is preferably performed for 10 minutes or less.

[0015] The lithium precursor may be added to the ratio between lithium and other metals in the original active material used in the active material layer in accordance with the ratio of lost lithium through the washing.

[0016] The annealing may be performed in air at 400° C. to 1000° C.

[0017] The temperature of the annealing step may exceed the melting point of the lithium precursor.

[0018] The active material in the active material layer may be collected in a powder form, and carbon generated by carbonization of the binder or the conductive material may not remain on the surface.

[0019] The reusable active material may have a similar particle size distribution as the active material in the active material layer.

[0020] The reusable active material may have a fluorine (F) content of 100 ppm or less.

[0021] Another method for recycling positive active materials according to the present disclosure includes: (a) heat treating positive electrode waste at 300° C. to 650° C. in air for 1 hour or less, wherein the positive electrode waste is left after punching out a positive electrode plate in a positive electrode including a lithium cobalt oxide positive electrode active material layer on a current collector, wherein the heat treatment is performed to thermally decompose a binder and a conductive material in the active material layer to separate the current collector from the active material layer, and to collect the active material in the active material layer; (b) washing the collected active material with a lithium precursor aqueous solution for 10 minutes or less, and drying, wherein the lithium precursor aqueous solution is alkaline in the aqueous solution and the content of the lithium precursor is greater than 0% and less than 15%; and (c) annealing the washed active material at 400° C. to 1000° C. in air without adding additional lithium precursor.

[0022] Beneficial effects

[0023] According to the present disclosure, it is possible to reuse discarded positive electrode active materials (such as positive electrode waste generated during the manufacture of lithium secondary batteries) without using acid, thereby achieving environmental protection. The method according to the present disclosure does not require a neutralization process or a wastewater treatment process, thereby achieving environmental mitigation and reducing process costs.

[0024] According to the present disclosure, all metal elements of the positive electrode active material can be collected. Since the current collector is not dissolved, the current collector can be collected. The extracted active material elements are not used as raw materials for synthesizing the positive electrode active material, and the active material collected in the form of powder is directly reused, thereby achieving economic benefits.

[0025] According to the present disclosure, safety is achieved because toxic and explosive solvents such as NMP, DMC, acetone, and methanol are not used, and simple processes such as heat treatment, washing, and annealing are used, so it is easy to manage and suitable for large-scale production.

[0026] Furthermore, according to the present disclosure, the LiF and Co bonds can be prevented by heat treatment for a short time (1 hour or less). 3O 4 The battery characteristics of the recovered active materials are restored by shortening the surface modification time (10 min or less) in the washing process using an aqueous lithium precursor solution to reduce lithium dissolution caused by surface modification, and restoring the crystal structure through subsequent high-temperature annealing. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings illustrate embodiments of the present disclosure and, together with the following detailed description, help to further understand the technical aspects of the present disclosure, and thus the present disclosure should not be construed as being limited to the accompanying drawings.

[0028] Figure 1 The figure shows the positive electrode scraps discarded after punching out the positive electrode plates in the positive electrode sheet.

[0029] Figure 2 is a flow chart of an active material recycling method according to the present disclosure.

[0030] Figure 3 The results of battery evaluation using the active materials of Examples and Comparative Examples are shown.

[0031] Figure 4 X-ray photoelectron spectroscopy (XPS) patterns of active materials of Examples and Comparative Examples are shown.

[0032] Figure 5 X-ray diffraction (XRD) patterns of active materials of Examples and Comparative Examples are shown.

[0033] Figure 6 The following are scanning electron microscope (SEM) photographic images of the active materials of Examples and Comparative Examples.

[0034] Figure 7 It is a graph showing the particle size distribution of the active materials of Examples and Comparative Examples. DETAILED DESCRIPTION

[0035] Hereinafter, the embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Before the description, it should be understood that the terms or words used in the specification and the appended claims should not be interpreted as being limited to the general and dictionary meanings, but are interpreted according to the meanings and concepts corresponding to the technical aspects of the present disclosure based on the principle that the inventor is allowed to appropriately define the terms to obtain the best interpretation. Therefore, the embodiments described herein and the illustrations shown in the figures are only examples and do not fully describe the technical aspects of the present disclosure, so it should be understood that various other equivalents and modifications may be made to them when filing a patent application.

[0036] In the following description, reference is made to the accompanying drawings which form a part of the present disclosure. The embodiments described in the detailed description, drawings, and appended claims are not intended to be limiting. Other embodiments may be used, and modifications and changes may be made thereto, without departing from the technical aspects and scope of the subject matter disclosed herein. As generally described herein and illustrated in the accompanying drawings, aspects of the present disclosure may include arrangements, substitutions, combinations, and designs of various different elements, and it will be immediately understood that all such elements are expressly contemplated.

[0037] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs (hereinafter referred to as "person skilled in the art").

[0038] The present disclosure is not limited to the specific embodiments described herein. It is obvious to those skilled in the art that many variations and changes may be made to the present disclosure without departing from the technical aspects and scope of the present disclosure. For those skilled in the art, in addition to those methods listed herein, functionally equivalent methods within the scope of the present disclosure are apparent from the foregoing description. Such variations and changes fall within the scope of the appended claims. The scope of all equivalents to which the present disclosure and the appended claims are entitled will be defined by the appended claims. It should be understood that the present disclosure is not limited to specific variant methods. It should be further understood that the terms used herein are intended to describe specific embodiments, rather than to limit the present disclosure.

[0039] The traditional active material recycling process is mainly to extract the valuable metal (nickel, cobalt, manganese) elements in the lithium secondary battery active materials whose performance has deteriorated after use, and resynthesize the active materials. Compared with the traditional process, the feature of the present invention is to collect active materials from the positive electrode waste generated in the lithium secondary battery manufacturing process.

[0040] In addition, well-known active material recycling processes involve producing metals (direct reduction method) or resynthesizing active materials from valuable metals extracted by acid / base dissolution or melted using reducing agents / additives, which requires additional chemical methods, complicates the process, and causes additional economic expenditure. However, the present disclosure relates to a method for directly recycling positive electrode active materials without dissolving the positive electrode active materials.

[0041] In order to directly reuse the positive electrode active material, it is necessary to remove the current collector from the positive electrode. The current collector can be removed from the positive electrode by high temperature heat treatment to remove the binder, using a solvent to melt the binder, melting the current collector, and screening the active material by dry grinding and sieving.

[0042] When a solvent is used to melt the binder, the stability of the solvent is important. NMP is the most effective solvent, but its disadvantages are toxicity and high cost. Another disadvantage is that a waste solvent reprocessing or solvent collection process must be performed. The process cost required to melt the current collector is lower than that of using a solvent. However, it is difficult to remove impurities from the surface of the reusable active material, and hydrogen is produced in the process of removing the current collector, posing a risk of explosion. Dry grinding and screening cannot perfectly separate the current collector and active material. The particle size distribution of the active material changes during the grinding process, and it is difficult to remove the binder, resulting in a decrease in the characteristics of the battery including the reusable active material.

[0043] The present disclosure uses a high temperature heat treatment to separate the active material from the current collector. In particular, the heat treatment is performed in air, so the process only requires heating without any special device configuration, and is therefore relatively simple and suitable for large-scale production and commercialization. However, impurities should not remain on the surface of the reusable active material. The present disclosure proposes a step of removing impurities from the surface of the reusable active material.

[0044] In the following, reference will be made to Figure 2 An active material recycling method according to one embodiment of the present disclosure is described. Figure 2 is a flow chart of an active material recycling method according to the present disclosure.

[0045] refer to Figure 2 First, discarded positive electrode scrap is prepared (S10).

[0046] As mentioned above Figure 1 The positive electrode waste may be what is left after manufacturing a positive electrode sheet including a positive electrode active material layer on a current collector and punching a positive electrode sheet. In addition, the positive electrode waste may be prepared by collecting positive electrodes with defects or failures in the process. In addition, the positive electrode waste may be prepared by separating positive electrodes from lithium secondary batteries discarded after use.

[0047] For example, the cathode waste may be what is left after the following process: coating a sheet-like current collector of aluminum foil with lithium cobalt oxide (such as LiCoO 2 A slurry is prepared by mixing carbon (such as carbon black, etc.) as a conductive material, polyvinylidene fluoride (PVdF, etc.) as a binder with N-methylpyrrolidone (NMP); drying in a vacuum oven at about 120°C to manufacture a positive electrode sheet; and punching the positive electrode plate into a predetermined size.

[0048] The positive electrode waste has an active material layer on a current collector of a metal foil such as an aluminum foil. The active material layer is formed by applying a slurry including a mixture of an active material, a conductive material, a binder and a solvent, and after the solvent is volatilized, the active material and the conductive material are combined with the binder. Therefore, when the binder is removed, the active material can be separated from the current collector.

[0049] Subsequently, the positive electrode waste is milled into an appropriate size (S20). Milling refers to cutting or chopping the positive electrode waste into an appropriate size for disposal. After milling, the positive electrode waste is cut into, for example, 1 cm×1 cm. Various dry milling equipment can be used in milling, including a hand mill, a pin mill, a disc mill, a cutting mill and a hammer mill as well as a high-speed cutter.

[0050] Milling can be performed considering the characteristics required by the equipment used in the disposal and subsequent processes of the cathode waste. For example, when equipment that requires continuous processing is used to load and unload cathode waste, it is necessary to mill the oversized cathode waste to facilitate the movement of the cathode waste.

[0051] Subsequently, the cathode waste is heat-treated in air ( S30 ).

[0052] In the present disclosure, the heat treatment is performed to thermally decompose the binder in the active material layer. The heat treatment may be performed at 300°C to 650°C and may be referred to as a high temperature heat treatment. At a temperature below 300°C, it is difficult to remove the binder, making it impossible to separate the current collector, while at a temperature of 650°C or above, the current collector melts (Al melting point: 660°C), making it impossible to separate the current collector.

[0053] The heat treatment time is sufficient to cause the binder to thermally decompose. For example, the heat treatment time is about 30 minutes. Preferably, the heat treatment time is 30 minutes or longer. As the heat treatment time increases, the thermal decomposition time of the binder will be extended, but when the heat treatment time is equal to or longer than the predetermined time, there is no difference in the thermal decomposition effect. Preferably, the heat treatment time is 30 minutes or longer and 5 hours or less. Most preferably, the heat treatment time is 1 hour or less. High temperature heat treatment removes the binder and the conductive material, generating CO 2 and H 2 O,CO 2 and H 2 O reacts with lithium on the surface of the positive electrode active material to produce Li 2 CO 3 , LiOH, which in turn reacts with F present in the binder to produce LiF or metal fluoride. In addition, in the case of LCO active materials, Co can be produced on the surface by thermal decomposition. 3 O 4 When manufacturing batteries, Co 3 O4 The characteristics of the battery may be degraded if left on the surface. A heat treatment time of 1 hour or less can prevent the generation of impurities that cause loss of lithium such as LiF and degrade the performance of the secondary battery if left. In particular, a heat treatment of 1 hour or less can prevent Co 3 O 4 The production of.

[0054] The heat treatment equipment may include various types of furnaces. For example, the heat treatment equipment may be a box-type furnace, and in consideration of productivity, may be a rotary kiln capable of continuous treatment.

[0055] After heat treatment, the product can be cooled quickly or slowly in air.

[0056] For example, the heat treatment can be performed at 600°C for 30 minutes with a temperature rise rate of 5°C / minute. For example, the temperature rise rate is within the allowable range of the box furnace and is sufficient to heat the positive electrode waste without generating thermal shock. 600°C is set in consideration of the melting point of the aluminum current collector and for good thermal decomposition of the binder. When the heat treatment is performed at the above temperature for less than 10 minutes, the thermal decomposition is insufficient, so it is necessary to perform a heat treatment for 10 minutes or longer, preferably 30 minutes or longer. At this temperature, a 30-minute heat treatment promotes sufficient thermal decomposition of the binder and the conductive material and prevents the generation of LiF and Co. 3 O 4 .

[0057] Through the heat treatment in air, the binder and the conductive material in the active material layer are thermally decomposed to convert CO 2 and H 2 O is removed. Since the binder is removed, the active material can be separated from the current collector, and the active material to be collected can be screened out in the form of powder. Therefore, the current collector can be separated from the active material layer, and the active material in the active material layer can be collected by S30.

[0058] It is important to perform the heat treatment of S30 in air. When heat treated in a reducing or inert gas environment, the binder and the conductive material undergo carbonization rather than thermal decomposition. When carbonized, carbon remains on the surface of the active material and degrades the performance of the reusable active material. When heat treated in air, the carbon in the binder or conductive material generates CO, CO2, and CO3 by a combustion reaction with oxygen. 2 The gas is removed, so the adhesive and conductive material will not remain and are almost completely removed.

[0059] Therefore, according to the present disclosure, the active material is collected in the form of powder, and carbon generated by carbonization of the binder or the conductive material may not remain on the surface.

[0060] Subsequently, the collected active material is washed and dried (S40). It is important to wash with an aqueous lithium precursor solution that is alkaline in aqueous solution. The aqueous lithium precursor solution contains a lithium precursor, preferably LiOH, in an amount of more than 0% and less than 15%. Preferably, less than 15% LiOH is used. When an excess of LiOH is included, the excess LiOH may remain on the surface of the active material after washing, which may affect the subsequent annealing process. In order to make the surface of the active material as clean as possible before annealing, it is not advisable to add excess LiOH, and the amount of LiOH is limited to less than 15%.

[0061] Washing can be performed by soaking the collected active material in a lithium precursor aqueous solution. Washing includes soaking the active material in an aqueous lithium precursor aqueous solution that is alkaline in the aqueous solution and stirring it while soaking. It is best to soak and stir together. When the active material is soaked in a lithium precursor aqueous solution without stirring, the washing process is very slow, resulting in lithium dissolution. When stirring is performed together, the process time is minimized, so it is best to stir while soaking in the lithium precursor aqueous solution.

[0062] Longer washing times may reduce capacity due to excessive dissolution of lithium. Therefore, washing for 1 hour or less is preferred. Most preferably, washing for 10 minutes or less is preferred to minimize lithium dissolution.

[0063] After filtering, drying may be performed in an oven (convection type) in air. Washing with an aqueous solution of an alkaline lithium precursor is performed to remove LiF and metal fluorides that may be present on the surface of the collected active material and to perform surface modification. In the heat treatment process of S30, the binder and the conductive material in the active material layer are removed by CO 2 and H 2 O is removed by evaporation, and in the process, CO 2 and H 2 O reacts with lithium on the surface of the active material to produce Li 2 CO 3 , LiOH, and F (such as PVdF) present in the binder reacts with the metal element of the positive electrode active material to produce LiF or metal fluoride. When LiF or metal fluoride remains, the characteristics of the battery including the reusable active material will be reduced. The present disclosure adds a washing step of S40 to remove the reaction products that may be generated on the surface of the reusable active material in the heat treatment step (S30) to prevent impurities from remaining on the surface of the reusable active material.

[0064] In S40, it is important to wash with an aqueous lithium precursor solution that is alkaline in aqueous solution. When an aqueous sulfuric acid or hydrochloric acid solution is used instead of an aqueous lithium precursor solution that is alkaline in aqueous solution, F on the surface of the active material is washed away, but the performance of the reusable positive active material may be reduced due to the dissolution of transition metals (Co, Mg) present in the active material. Preferably, the role of the aqueous lithium precursor solution that is alkaline in aqueous solution used in the present disclosure is to remove trace amounts of binders that may remain after the thermal decomposition of S30, not to dissolve transition metals present in the active material, and to compensate for the amount of lithium dissolved during the washing process.

[0065] In particular, it is preferred that the ratio of lithium to other metals in the original active material used in the active material layer be added by the washing of S40 at the ratio of lithium loss. To this end, it is important to maintain the concentration of the lithium precursor aqueous solution and the washing time as mentioned above.

[0066] The heat treatment time of 1 hour or less in the previous step S30 can reduce the lithium loss in the active material, but a small amount of additional lithium loss may occur during the washing process. When lithium loss occurs during the heat treatment or washing process, the lithium precursor aqueous solution used in the washing process of S40 can compensate for the lost lithium.

[0067] Subsequently, annealing is performed without adding additional lithium precursor to the washed active material (S50). S50 produces a reusable active material.

[0068] By performing heat treatment for 1 hour or less and washing for 10 minutes or less in the previous steps S30 and S40, lithium loss in the active material can be prevented. Therefore, it is possible to omit the addition of an additional lithium precursor to compensate for lithium loss. Since the previous washing step (S40) compensates for lithium with a lithium precursor aqueous solution, there is no need to add an additional lithium precursor.

[0069] S50 restores the crystal structure of the active material through annealing, so that the properties of the reusable active material can be restored or improved to the level of fresh active material.

[0070] After the previous steps S30 and S40, the surface structure of the active material may be modified. In addition, in the case of LCO active material, Co 3 O 4 When manufacturing batteries, Co 3 O 4 The battery characteristics may be degraded if it remains on the surface. The present invention can restore the crystal structure and remove Co by S50 3 O 4 , so that the initial properties are restored or improved to a level similar to that of fresh active materials.

[0071] Annealing can be performed at 400°C to 1000°C in air. The annealing temperature can be 600°C to 900°C. The temperature varies within a limited range, depending on the type of lithium precursor. The annealing time can be at least 1 hour. Preferably, the annealing time is about 5 hours. When the annealing time is long, the crystal structure may be fully restored, but long-term annealing does not have a great effect on the performance. For example, the annealing time is about 15 hours or less. The annealing equipment can be similar to or the same as the equipment of the heat treatment step S30.

[0072] For example, when LiOH is used as a lithium precursor in S40, the annealing temperature of S50 is preferably 400° C. to 600° C., more preferably 450° C. to 480° C. This is because the melting point of LiOH is 462° C.

[0073] Preferably, the annealing temperature is higher than the melting point of the lithium precursor. However, at a temperature higher than 1000°C, the positive electrode active material will undergo thermal decomposition and the performance of the active material will be reduced, so the annealing temperature should not exceed 1000°C.

[0074] According to the present disclosure, LiF or metal fluoride is removed in the washing step of S40, and Co is removed in the annealing step of S50. 3 O 4 The washing and drying steps using an aqueous lithium precursor solution that is alkaline in aqueous solution are safe and inexpensive, and can remove LiF or metal fluoride without losing other elements, prevent the dissolution of transition metals, and compensate for the lithium loss that occurs in this process. The annealing step is also safe and inexpensive, and can effectively remove Co 3 O 4 and restore the crystal structure (ie, increase the crystallinity), thereby improving the battery characteristics of the reusable active material.

[0075] Through S40, the present disclosure can adjust the LiF content on the surface of the collected active material to less than 500 ppm, thereby improving the capacity. Preferably, the F content can be less than 100 ppm. More preferably, the F content can be 30 ppm or less.

[0076] The reusable active material obtained according to the present disclosure can have a similar particle size distribution as the active material in the active material layer present in the positive electrode waste, and does not need to be treated separately. Since the carbon generated by the carbonization of the binder or the conductive material does not remain on the surface, there is no need to perform a carbon removal step. Figure 2 The active material obtained by the method can be used to manufacture the positive electrode without any treatment.

[0077] The reusable active material can be used 100% without adjusting the composition, or can be mixed with fresh LCO, and can be combined with a conductive material, a binder, and a solvent to prepare a slurry. According to the present disclosure, the battery characteristics of the recovered active material can be restored by annealing to restore the crystal structure. In addition, by reusing the positive active material in the discarded positive waste generated in the secondary battery manufacturing step, the process cost can be reduced.

[0078] Hereinafter, experimental examples of the present disclosure will be described in detail.

[0079] Experimental example

[0080] The positive electrode active materials were prepared by the methods of the following examples and comparative examples to evaluate the electrochemical performance.

[0081] Embodiment: Recyclable active materials are collected according to the active material recycling method of the present disclosure as described above. Positive electrode waste discarded after positive plate punching is prepared and heat-treated at 600°C for 30 minutes in S30. Washing of S40 is performed using LiOH for 10 minutes. In S50, annealing is performed in air at 750°C for 15 hours without adding additional lithium precursor.

[0082] Comparative Example 1: Fresh LCO was used, not a recyclable active material.

[0083] Comparative Example 2: As described above, in the active material recycling method of the present invention, by performing only the heat treatment of S30, the binder and the conductive material can be removed, the aluminum current collector can be separated, and the LCO active material can be collected. S30 is performed under the same conditions as in the embodiment. In the active material recycling method of the present invention, the surface modification of S40 and the crystal structure recovery of S50 are not performed.

[0084] Comparative Example 3: The method of Comparative Example 2 was repeated, but the heat treatment time in the heat treatment step S30 was 5 hours.

[0085] Comparative Example 4: On the basis of Comparative Example 2, LCO active material was collected by performing surface modification of S40 in the active material recycling method of the present disclosure as described above. That is, surface modification was performed, but crystal structure recovery of S50 in the active material recycling method of the present disclosure was not performed. S40 was performed under the same conditions as in the example.

[0086] 96 wt % of the positive electrode active material collected or prepared in the embodiments and comparative examples, 2 wt % of carbon black as a conductive material and 2 wt % of PVdF as a binder were measured and mixed with NMP to prepare a slurry, made into a positive electrode, and a battery (Coin Half Cell, CHC) was manufactured and the electrochemical performance was evaluated.

[0087] In order to find the amount of LiF remaining in the active materials collected in Example and Comparative Example 2, F was detected and analyzed using ICP. The results are shown in Table 1 below.

[0088] [Table 1]

[0089] Comparative Example 2 Example F content (mg / kg) 1900 ND

[0090] ND indicates that the measured F content is less than 30 ppm. Referring to Table 1 above, it can be seen that the F content in the positive electrode active material collected in Example 2 is much lower than that in Comparative Example 2. That is, it can be seen that LiF is completely dissolved in the lithium compound solution by washing and is completely removed so that it cannot be detected by ICP. Therefore, it can be seen that S40 has a very good removal effect on LiF.

[0091] ICP analysis was performed on the positive electrode active material collected or prepared in each Example and Comparative Example to analyze the amount of specific elements. The results are shown in Table 2 below.

[0092] [Table 2]

[0093] Al content (wt%) Comparative Example 1 0.33 Comparative Example 2 0.33 Comparative Example 4 0.33 Example 0.33

[0094] As seen in Comparative Example 1, the fresh active material used in the experiment further includes Al. It can be seen that Comparative Example 2 has undergone heat treatment, but the Al content has not changed, and the Al content is also maintained unchanged in Comparative Example 4 and the Examples that further include subsequent process steps. According to the present disclosure, it can be seen that LiF or metal fluorides can be removed without losing other elements (such as Al) and preventing the dissolution of transition metals.

[0095] Figure 3 Results of battery evaluation using active materials of Examples and Comparative Examples are shown. Capacity as a function of cycle number was evaluated at different currents to determine rate performance. The equipment used for evaluation is a charge and discharge tester commonly used in laboratories. There is no difference in measuring equipment or methods. Figure 3 In the graph, the horizontal axis is the number of cycles and the vertical axis is the capacity.

[0096] The voltage was 3 to 4.5 V, and the initial formation charge / discharge was performed at 0.2 C / 0.2 C. The electrolyte solution of the battery was a carbonate-based electrolyte solution, and included ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 3:7, and additives were added.

[0097] refer to Figure 3 , the lowest rate performance was found in Comparative Example 2 including the recyclable active material without surface modification and crystal structure recovery according to the present disclosure. This is because the binder and the conductive material are removed during the high temperature heat treatment process of S30, generating CO2 and H 2 O, which react with lithium on the surface of the positive electrode active material to produce Li 2 CO 3 and LiOH, Li 2 CO 3 The LiOH reacts with the F in the binder to produce LiF or metal fluoride on the surface of the active material which can be reused. In addition, the low battery performance is probably due to the presence of Co on the surface of LCO due to thermal decomposition. 3 O 4 Because of this.

[0098] Comparative Example 4 was surface-modified compared to Comparative Example 2. It was evaluated that Comparative Example 4 had better results than Comparative Example 2 because the reaction product on the surface was removed by washing.

[0099] Compared with Comparative Example 4, the embodiment was annealed. It was found that the modified structure of the active material surface and the Co 3 The reduction of O4 to the LCO crystal structure produces better results than the initial characteristics of the fresh active material of Comparative Example 1. According to the present disclosure, it is possible to collect active materials at directly usable levels from cathode waste. Since no toxic and explosive solvents such as NMP, DMC, acetone and methanol are used, and simple and safe methods such as heat treatment, washing and drying, and annealing are used, it is suitable for large-scale production.

[0100] Figure 4 The XPS patterns of the active materials of the embodiments and comparative examples are shown. In the XPS pattern, the horizontal axis represents the binding energy (unit: eV). The XPS pattern can be obtained using an XPS measuring instrument commonly used in the laboratory. For example, the K-Alpha obtained from Thermo Fisher Scientific can be used for analysis. The F present in the binder reacts with the Li of the active material in the heat treatment process to produce LiF. Figure 4In the figure, the peak around 684eV is caused by LiF, and for each sample, the higher intensity represents the presence of a larger amount of LiF on the surface of the positive active material. Since the XPS pattern of Comparative Example 1 was measured with fresh LCO, the presence of LiF was not measured. However, Comparative Example 2 shows the presence of LiF generated on the surface of the active material during the heat treatment process. In Comparative Example 3, since the heat treatment time was increased to 5 hours, the F generated increased compared to Comparative Example 2, and the amount of LiF generated on the surface of the active material increased, so the LiF peak intensity of XPS was measured higher than that of Comparative Example 2. Since the amount of LiF present on the surface of the active material is the cause of the degradation of battery characteristics, it is necessary to remove LiF. Compared with Comparative Example 2, the embodiment removes LiF by washing, and the XPS results show no peak of LiF.

[0101] Figure 5 The XRD patterns of the active materials of the embodiments and comparative examples are shown. In the XRD pattern, the horizontal axis is 2θ (Theta) (degrees, °), and the vertical axis represents intensity. The XRD pattern can be obtained using an X-ray diffractometer commonly used in laboratories. For example, a Rigaku X-ray diffractometer XG-2100 can be used for analysis. However, there is no difference in measuring equipment or methods.

[0102] Figure 5 (a) shows the XRD pattern of Comparative Example 1 (ie, fresh LCO). Figure 5 (b) is the XRD pattern of the active material of Comparative Example 2, and Figure 5 (c) is the XRD pattern of the active material of Comparative Example 3. Figure 5 (d) shows the XRD pattern of the active material of the example. When (b) and (c) are compared with (a), it can be observed that Co generated during the heat treatment process 3 O 4 Phase. 3 O 4 It is produced on the surface of the active material, that is, on the surface of LCO in the heat treatment process. Therefore, it can be seen that in the heat treatment process of S30, Co is produced on the surface of LCO. 3 O 4 .

[0103] Figure 5 (d) is the XRD pattern of the active material of the embodiment. When (b) and (c) are compared with (d), it is verified that Co 3 O 4 This is because during the S50 annealing process, the LiOH remaining on the surface of the active material in the S40 washing process is removed by the Co 3 O 4 The reaction produces LCO, and Co3 O 4 was removed.

[0104] Through XPS and XRD pattern analysis, it can be seen that the results of the embodiment are similar to those of Comparative Example 1. Therefore, it is verified that the recovery of the embodiment of the present disclosure reaches the level of fresh active material of Comparative Example 1. According to the present disclosure, it is possible to collect directly reusable active materials from positive electrode waste.

[0105] Figure 6 It is a scanning electron microscope (SEM) photographic image of the active material of the embodiment and the comparative example. This SEM photographic image is taken using a SEM device commonly used in the laboratory. For example, HITACHI s-4200 can be used for imaging. However, there is no difference in the measurement equipment or method.

[0106] Figure 6 (a) is a SEM photographic image of fresh LCO of Comparative Example 1, and Figure 6 (b) is a SEM photographic image of the reusable active material of the embodiment. It can be seen that the LCO collected in the embodiment shows the same shape as the fresh LCO. In addition, only LCO was observed, which reveals that the binder and the conductive material were removed in the high-temperature heat treatment process. Therefore, it can be seen that the active material is separated from the current collector by heat treatment in the air, and almost no binder or conductive material remains on the surface of the active material. According to the present disclosure, it is possible to separate the current collector from the active material without using complex methods or harmful materials, thereby collecting the active material in an environmentally friendly manner. Since no acid is used, no neutralization process or wastewater treatment process is required, thereby achieving environmental mitigation and process cost reduction.

[0107] Figure 7 : is a particle size distribution diagram of the active materials of the embodiment and the comparative example. The particle size distribution can be obtained using a particle size analyzer commonly used in the laboratory. For example, it can be measured using a Horiba LA 950V2 particle size analyzer. However, there is no difference in the measurement equipment or method. Figure 7 In FIG. 1 , the horizontal axis represents the particle size (μm), and the vertical axis represents the volume (%).

[0108] All active materials collected in Examples and Comparative Examples 2, 3, and 4 have similar particle size distributions compared to the fresh LCO of Comparative Example 1. The particle size distributions are defined as similar when the difference in volume % of particles having the same particle size is within the range of + / -2%. According to the present disclosure, since the particle size distribution of the active material does not change and the initial characteristics are almost maintained, it is expected that the characteristics of the battery including the recycled active material will be at a similar level to those of the battery using the fresh active material.

[0109] According to the present disclosure, cathode waste can be recycled using a simple, environmentally friendly, and economical method, and a lithium secondary battery manufactured by recycling the prepared LCO cathode active material has no problem in terms of battery performance.

[0110] Although the present disclosure has been described herein with respect to limited embodiments and drawings, the present disclosure is not limited thereto, and it will be apparent to those skilled in the art that various modifications and changes may be made thereto within the technical aspects of the present disclosure and the scope of the appended claims and their equivalents.

Claims

1. A method for recycling positive electrode active materials, the method comprising the following steps: (a) heat-treating a positive electrode waste including a lithium cobalt oxide positive electrode active material layer on a current collector in air to thermally decompose a fluorine-containing binder and a conductive material in the active material layer to separate the current collector from the active material layer, and collecting the active material in the active material layer; (b) washing the collected active material with an aqueous lithium precursor solution which is alkaline in aqueous solution, and drying; as well as (c) annealing the washed active material without adding additional lithium precursor to obtain a reusable active material, Wherein, the heat treatment is performed at 300° C. to 650° C. for no more than 1 hour.

2. The method for recycling positive electrode active materials according to claim 1, wherein: The content of the lithium precursor in the lithium precursor aqueous solution is at most 15%, and the washing is performed for no longer than 10 minutes.

3. The method for recycling positive electrode active materials according to claim 1, wherein: The washing is performed by stirring the collected active material while being immersed in the lithium precursor aqueous solution.

4. The method for recycling positive electrode active materials according to claim 2, wherein: The lithium precursor includes LiOH.

5. The method for recycling positive electrode active materials according to claim 1, wherein: The ratio between lithium and other metals in the original active material used in the active material layer is adjusted according to the ratio of lithium lost by the washing.

6. The method for recycling positive electrode active materials according to claim 1, wherein: The annealing is performed in air at 400° C. to 1000° C.

7. The method for recycling positive electrode active materials according to claim 1, wherein: The temperature of the annealing step exceeds the melting point of the lithium precursor.

8. The method for recycling positive electrode active materials according to claim 1, wherein: The active material in the active material layer is collected in a powder form, and carbon generated by carbonization of the binder or the conductive material does not remain on the surface.

9. The method for recycling positive electrode active materials according to claim 1, wherein: The recyclable active material has a similar particle size distribution as that of the active material in the active material layer.

10. The method for recycling positive electrode active materials according to claim 1, wherein: The reusable active material has a fluorine (F) content of 100 ppm or less.

11. A method for recycling positive electrode active materials, the method comprising the following steps: (a) subjecting a positive electrode waste to a heat treatment at 300° C. to 650° C. for no more than 1 hour in air, the positive electrode waste being the positive electrode plate remaining after punching out a positive electrode including a lithium cobalt oxide positive electrode active material layer on a current collector, wherein the heat treatment is performed to thermally decompose a fluorine-containing binder and a conductive material in the active material layer to separate the current collector from the active material layer, and to collect the active material in the active material layer; (b) washing the collected active material with an aqueous lithium precursor solution for no more than 10 minutes and drying, wherein the aqueous lithium precursor solution is alkaline in the aqueous solution and the content of the lithium precursor is at most 15%; as well as (c) The washed active material is annealed at 400° C. to 1000° C. in air without adding additional lithium precursor.

Citation Information

Patent Citations

  • Automated local story generation and curation

    KR1020200062372A

  • Recovery method of positive electrode leftover material of lithium-ion battery

    CN105895854A